ADSORPSI LOGAM BERAT LIMBAH CAIR TEKSTIL MENGGUNAKAN ZEOLIT DAN FLY ASH KELAPA SAWIT - Elda Pelita; Rita Youfa; Dyah Nirmala; - Desniorita; Regna Tri Jayanti; Resi Levi Permadani; Dwimaryam Suciati (Texere, 2026)
Reducing heavy metal concentrations in wastewater remains a major challenge in industrial waste treatment, including textile wastewater. One effective and economical method is filtration using porous adsorbent media. This study aimed to evaluate the effectiveness of filtration media based on palm oil mill fly ash and zeolite in reducing heavy metal concentrations in textile wastewater. The filtration process was carried out using a layered filter system with four different media arrangement models to adsorb pollutants from wastewater. The results showed that the filtration system significantly reduced heavy metal concentrations, with an average removal efficiency of 85%. The quality of wastewater after filtration using fly ash and zeolite media with pH of 7, TSS of 0.2 mg/L, and Cr concentration of 0.065 mg/L. The best filtration performance was achieved by Model A, with the media arrangement consisting of (1) coarse zeolite, (2) fine zeolite, (3) fly ash, and (4) cotton fiber. This media combination has strong potential as a simple, effective, and environmentally friendly technology for textile wastewater treatment.